Approaches for Bridging Research and Industry - Hamburg, Ileana; Bucksch, Sascha (Archives of Business Research, 2016)
The collaboration between research and industry facilitating knowledge transfer is underdeveloped particularly referring small and medium sized enterprises (SMEs). Some reasons for this situation are lack of interest from research and education institutions to support companies, poor capabilities of SMEs to recognise the importance of innovation for their businesses and competitiveness and to engage in knowledge transfer activities, existing of practical approaches that support research abut not the transfer of research results to SMEs. In these paper two approaches applied by the authors in two European projects are presented contributing to bridge research institutions and SMEs: creating practical applications of academic knowledge for entrepreneurs which are focused on the success of their business and motivate people to work together and working partnerships between industry, research and education helping SMEs to use new technologies.